Diagnosis of endocardial cushion defect with cross-sectional and M-mode scanning echocardiography. Differentiation from secundum atrial septal defect. Issue 9 (September 1976) - Beppu, S; Nimura, Y; Nagata, S; Tamai, M; Matsuo, H
Abstract : Twelve cases of endocardial cushion defect were studied before and after operation with ultrasono-cardiotomography (tomography) cross-sectional echocardiography, two-dimensional echocardiography, B-scan echocardiography) and M-mode scan along a horizontal section of the heart. For comparison, 20 healthy subjects, 18 cases of mitral valvular disease, 4 cases of congestive cardiomyopathy, 1 case of partial anomalous pulmonary venous drainage, and 25 cases of atrial septal defect of secundum type were also examined with the same technique. In cases without cardiac malformation, the echo of the anterior mitral valve was usually continuous medially with that of the interatrial septum in the horizontal plane at the level of the membranous septum. This feature was clearly recorded in all cases with right heart enlargement. In ostium secundum atrial septal defect the echo of the anterior mitral valve continued into that of the interatrial septum. An echo interruption was shown, indicating the defect itself to be in the middle part of the interatrial septum. In all the cases of endocardial cushion defect which we examined discontinuity was shown between the echo of the anterior mitral valve and that of the interatrial septum. This discontinuity was interpreted as indicating the defect itself. The mitral valve ring echo was close to the basal end of that of the interventricular septum, possibly reflecting an abnormal attachment of the mitral valve. In all cases, after operation, the echo of the artificial interatrial septum was recorded, continuous with that of the anterior mitral valve. The features of the echocardiographic sweep from the anterior mitral valve to the interatrial septum were thus different in the three groups. These echocardiographic differences are thought to correspond to the anatomical differences between the normal, atrial septal defect of secundum type, and endocardial cushion defect, and are essential features differentiating them from each other.